Dealing with prostate cancer? Don't let histiocytic lesions fool you! - Maiara Ferreira de Souza; Diogo Diniz de Moraes; Talita Porto da Costa; Juarez Araújo Andrade; Huarne João José Tenório de Macêdo; Augusto Paraíso; Daniel Abensur Athanazio (BMC, 2020)
Abstract Background Prostate adenocarcinoma has well known benign mimickers. Histiocytic proliferations usually impose differential diagnosis with high-grade component of acinar adenocarcinoma (Gleason pattern 5). Case presentation We present herein three cases of histiocytic lesions of the prostate in which accurate recognition avoided inappropriate upgrading (malakoplakia associated with prostate adenocarcinoma, two cases) and false positive diagnosis at biopsy (xanthoma with signet ring morphology). Conclusion In needle biopsies, pathologists should have a low threshold to perform immunostains when considering a differential diagnosis between high-grade carcinoma and a histiocytic lesion. In prostatectomy specimens, abrupt transition to solid areas in low and intermediate grade tumors should raise concern to exclude malakoplakia. PAS and von Kossa stains are inexpensive and a valuable tool to highlight typical Michaelis-Gutmann bodies.